2022
DOI: 10.3390/nu14040868
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Measures of Sarcopenia in Developing Economies: A Systematic Review

Abstract: Sarcopenia refers to common age-related changes characterised by loss of muscle mass, strength, and physical performance that results in physical disability, poorer health status, and higher mortality in older adults. Diet quality is indicated as a potentially modifiable risk factor for sarcopenia. However, the association between diet quality and sarcopenia in developing economies appears to be conflicting. Hence, we conducted a systematic review of the literature from developing economies examining the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…People with a high diet quality usually have more diversified eating habits. In a systematic review of diet quality and sarcopenia in developing economies, diet quality defined by diversity and nutrient adequacy was found to be positively associated with the components of sarcopenia (muscle mass, muscle strength, and physical performance) ( 27 ). Although dietary variety analyses do not necessarily take into account the “healthfulness” of foods within food groups as diet quality or patterns (such as Mediterranean diet), most dietary guidelines recommend adding a variety of foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with a high diet quality usually have more diversified eating habits. In a systematic review of diet quality and sarcopenia in developing economies, diet quality defined by diversity and nutrient adequacy was found to be positively associated with the components of sarcopenia (muscle mass, muscle strength, and physical performance) ( 27 ). Although dietary variety analyses do not necessarily take into account the “healthfulness” of foods within food groups as diet quality or patterns (such as Mediterranean diet), most dietary guidelines recommend adding a variety of foods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between diet and sarcopenia (7,13,18,(26)(27)(28)(29). There is, however, a lack of evidence from developing countries, as most of these studies were based on data from developed countries (23).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate nutrient intake is important for maintaining muscle strength [39]. A systematic review also reported that nutrient sufficiency is positively correlated with sarcopenia-related parameters such as muscle strength and muscle mass [40]. Therefore, the Japanese dietary pattern adherence might contribute to handgrip strength maintenance through better nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, incidence of age-related sarcopenia is also on the rise, and it has become an important focus of geriatric research 2 . Sarcopenia is defined as the age-related loss of indicators of skeletal muscle quality, including muscle mass, strength and physical performance 3 . In older adults, sarcopenia is associated with an increase in adverse outcomes, including falls, functional decline, weakness and death 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%